Drug-Induced Nodular Regenerative Hyperplasia - Ghabril, Marwan; Vuppalanchi, Raj (Seminars in Liver Disease, 2014)
Drug-induced nodular regenerative hyperplasia is an uncommon injury with unique pathophysiology, clinical, and diagnostic considerations. This injury is characteristically asymptomatic in its early phases with only mild elevations in transaminases (< 3× upper limit of normal [ULN]). The latency period is typically more than 6 months. Once clinically apparent, it is marked by complications of portal hypertension, including hypersplenism, ascites, and variceal bleeding, with little or no hepatic dysfunction. Hence, it is an important cause of noncirrhotic portal hypertension. The most commonly associated drugs include thiopurines, chemotherapeutic agents, and antiretroviral agents. Diagnosis is aided by the recognition of noncirrhotic portal hypertension, a detailed history of prior drug exposure, and exclusion of the other causes of nodular regenerative hyperplasia. Clinical history, abdominal imaging, and hepatic hemodynamic studies provide important diagnostic clues, but histologic examination remains the diagnostic gold standard. Therapeutic intervention is aimed at earliest discontinuation of the offending agent and of portal hypertension complications. The natural history varies widely, and portal hypertension can progresses despite drug discontinuation.
Keywords: nodular regenerative hyperplasia; drug-induced liver injury